TEORI PEMBELAJARAN EXPERIENTAL PADA MATA PELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH - Siti Umroh (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this article is to discuss the application of experiential learning theory in foreign language learning, namely Arabic and English to help students understand and apply Arabic. Arabic is one of foreign language subjects that must be mastered by students, especially students in the madrasa environment. In the learning process, many students experience difficulties related to the students' memory of the knowledge they have acquired. Students receive knowledge but after a few days they forget the knowledge they have acquired. This happens because the knowledge gained has not yet entered their long term memory. The second problem is that students find it difficult to remember vocabulary in Arabic. Through learning with this experiential theory, students become easier to understand concepts and help develop skills in Arabic material